The relationships between teachers’ emotional health and stress coping - Emeljanovas, Arūnas; Sabaliauskas, Stanislav; Mežienė, Brigita; Istomina, Natalja (Frontiers in Psychology, 2023)
Introduction Teaching is a profession that involves challenges to emotional health. Teachers experience high levels of work-related stress, which causes symptoms such as anxiety, depression and burnout. Teachers’ mental health affects not only their own well-being, but also the quality of education and student achievement. Coping strategies can effectively improve teachers’ emotional health. The aim of this study is to assess the relationship between teachers’ emotional health and stress coping. Methods The sample consisted of 385 teachers from Lithuania, with an average age of 50.2 (±9.62) years and 24.9 (±11.8) years of school experience. The WHO-5, the Kessler Psychological Distress Scale (K6), the Spanish Burnout Inventory, Educational Version (SBI-Ed) and the Coping Strategies Scale were used in the study. Results The study results show that teachers’ age, seniority, size of residence, and marital status do not affect their emotional health, but their financial situation and hobbies have a positive impact on enthusiasm. Effective coping strategies such as problem solving, exercise, and hobbies improve emotional well-being, whereas negative coping methods such as self-isolation and alcohol consumption lead to psychological distress and lower enthusiasm at work.